Advances in MEMS and microfluidic systems - Singh, Rajeev Kumar 1969-; Phanden, Rakesh Kumar; Sikarwar, Basant Singh; Davim, J. Paulo 1964- (IGI Global, 2023)
Advances in MEMS and Microfluidic Systems explores the emerging research and advances in MEMS device and microfluidic systems applications. It features in-depth chapters on microfluidic device design and fabrication as well as on the aspects of devices/systems, characterization, and comparative research findings. Covering topics such as biosensors, lab-on-a-chip, and microfluidic technology, this premier reference source is an indispensable resource for engineers, health professionals, students and educators of higher education, librarians, researchers, and academicians
Keywords: Microfluidics; Microelectromechanical systems